Contribution of diffusion weighted MRI to the differential diagnosis of renal masses - Kış, Naciye; Düzkalır, Hanife Gülden; Ağaçlı, Mehmet Oğuzhan; Erok, Berrin; Kılıçoğlu, Zeynep Gamze (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. We aimed to assess the usefulness of diffusion weighted imaging (DWI) and apparent diffusion coefficients (ADCs) for characterizing renal masses. Material and method. In this retrospective study we measured the ADC values of renal masses at b=0, b=500 and b=1000. Measurements were made by placing a circular region of interest with a diameter of 1 cm.ADC values from normal renal parenchyma were taken to define the ADC and to compare with the ADC values of the lesions. Results. A total of 72 lesions of 54 patients were included.40 of the masses were benign and 32 were malignant. The ADC values of benign lesions at both b values were significantly higher than malignant lesions. We found the lowest values in angiomyolipomas (AMLs) and oncocytomas and the highest values in Bosniac type I cysts. Similarities was found between the ADC values of some AMLs and the RCCs. In terms of statistical results, the inclusion of AMLs in the analysis did not significantly affect the difference between malignant and benign lesions. Conclusion. In our study, the ADC values of benign renal masses were higher than those of normal renal parenchyme, which is higher than those of malignant renal masses.The lowest ADC values were observed in AMLs and oncocytomas.
Keywords: apparent diffusion coefficient; diffusion weighted imaging; renal neoplasms